Clinical Characteristics, In Silico Analysis, and Intervention of Neonatal-Onset Inflammatory Bowel Disease With Combined Immunodeficiency Caused by Novel TTC7A Variants - Chen, Yun-e; Chen, Jingfang; Guo, Wenxing; Zhang, Yanhong; Li, Jialing; Xie, Hui; Shen, Tong; Ge, Yunsheng; Huang, Yanru; Zheng, Wenying; Lu, Mei (Frontiers in Genetics, 2022)
We aimed to explore the genotypic and phenotypic characteristics of neonatal-onset inflammatory bowel disease (IBD) with combined immunodeficiency due to TTC7A mutaion. We examined the clinical manifestations, imaging results, endoscopic and histological findings, interventions, and prognosis of a patient with neonatal-onset IBD and performed biochemical analyses, whole-exome sequencing (WES), and in silico analysis. Our patient developed severe early-onset diarrhea, malnutrition, electrolyte imbalance, dehydration, and recurrent infections after birth. Radiographic and ultrasonic images showed no specific manifestations. Endoscopic and histological examination revealed chronic inflammation. Immune function examination indicated immunodeficiency. WES identified compound heterozygous TTC7A mutations (c.2355+4A>G, c.643G>T) in the infant. No abnormal splicing sequence as a result of the c.2355+4A>G mutation was found in TTC7A expression analysis; however, its mRNA expression was reduced. The patient’s condition did not improve after treatment with methylprednisolone or leflunomide. The patient died when treatment was stopped at age 5 months and 19 days. Compound heterozygous mutations (c.2355+4A>G, c.643G>T) in the TTC7A gene are described and verified for the first time. Our report expands the phenotypic spectrum of TTC7A mutations and the genotypic spectrum of very early–onset IBD with combined immunodeficiency.